E-Agriculture and Rural Development
DOI: 10.4018/978-1-4666-2655-3.ch006
|View full text |Cite
|
Sign up to set email alerts
|

ICT in Agricultural Development

Abstract: The transformational role of ICT in the social and economic spheres of man engendered development of the communication technology in Nigeria. Based on the telecom deregulation policy of the Nigerian Government in 2001, the country witnessed an upsurge of private investment in ICT development and its consequential ICT revolution. An empirical survey of diffusion and adoption pattern of ICT in the Nigerian agricultural system showed that mobile phone constitutes the most widely adopted ICT device by the agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Finally, our study revealed that the likelihood of PC was higher among Christians than their Muslim counterparts particularly in countries in West Africa (Nigeria and Senegal) while in East African countries (Malawi and Rwanda) the reverse pattern was observed. Nigeria and Senegal have large Muslim population and among the religion, it is evidenced that early marriage was more common among Muslims than Christians (Adebowale et al, 2012). Early marriage is known to be a strong protective factor against premarital sex and PC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study revealed that the likelihood of PC was higher among Christians than their Muslim counterparts particularly in countries in West Africa (Nigeria and Senegal) while in East African countries (Malawi and Rwanda) the reverse pattern was observed. Nigeria and Senegal have large Muslim population and among the religion, it is evidenced that early marriage was more common among Muslims than Christians (Adebowale et al, 2012). Early marriage is known to be a strong protective factor against premarital sex and PC.…”
Section: Discussionmentioning
confidence: 99%
“…The VME is one of the very handy means of achieving this. This extension approach has been widely adopted and has proven to be helpful in educating and informing farmers of the need to adopt agricultural innovations and there are several success stories that allude to this (Abate et al, 2019;Karubanga et al, 2017;Lawal-Adebowale, 2012). VME can take various forms, such as documentaries, soap operas, comedies, and more.…”
Section: Introductionmentioning
confidence: 99%
“…Their biological values and domestic demand as the choicest milk and meat for consumers have been ranked higher than sheep and cattle [1]. Therefore, the need to increase goat production is a consequence of its capacity to generate income and improve the living standards of rural subsistence-farming communities [2] .The degree to which goats survive to marketable age is one of the key indicators for their efficient productivity. However, nutritional constraints remain a concern, because they limit; animal digestion and growth rate and weaken animals against parasitic and infectious diseases that bring about high mortality.…”
Section: Introductionmentioning
confidence: 99%